Rural homelessness : issues, experiences and policy responses - Cloke, Paul J.; Milbourne, Paul, 1966-; Widdowfield, Rebekah (Book collections on Project MUSE., 2002)
Rural homelessness explores the shifting policy context of homelessness and social exclusion in relation to rural areas in the UK and other countries in the developed world. Drawing on the first comprehensive survey of rural homelessness in the UK, the book positions these findings within a wider international context.